2012
DOI: 10.1074/jbc.m111.256586
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-containing Phosphotransfer Protein-B (HptB) Regulates Swarming Motility through Partner-switching System in Pseudomonas aeruginosa PAO1 Strain

Abstract: Background: This study investigates how histidine phosphotransfer protein-B (HptB) regulates Pseudomonas aeruginosa swarming. Results: HptB regulates the protein phosphatase activity of PA3346, which in turn controls the flagellar gene expression through interaction with PA3347. Conclusion: Our results reveal a partner-switching mechanism regulating the 28 -dependent motility genes. Significance: The interplay between a two-component system and 28 has been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 52 publications
4
73
1
3
Order By: Relevance
“…These results imply that HsbA has another major regulatory effect on denitrification. Indeed, it was reported that deletion of hsbA and site-directed mutagenesis to simulate constitutive activation of HsbA shared a hyperswarming phenotype (54). This is likely due to other regulatory effects that are not yet understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results imply that HsbA has another major regulatory effect on denitrification. Indeed, it was reported that deletion of hsbA and site-directed mutagenesis to simulate constitutive activation of HsbA shared a hyperswarming phenotype (54). This is likely due to other regulatory effects that are not yet understood.…”
Section: Resultsmentioning
confidence: 99%
“…One of these, Psest_1724 (hsbA) (w nitrate ϭ Ϫ1.6 [see Table S3 in the supplemental material]), had the largest w 9 nM MoϪreplete value (2.5) (see Table S4) of any gene and is annotated as an anti-sigma factor antagonist. In P. aeruginosa, HsbA binds the anti-sigma factor FlgM, thereby freeing sigma factor 28, FliA, to facilitate transcription of flagellar and other motility-related genes (54,55). RCH2 has two fliA homologs, Psest_1740 (fliA1) and Psest_4160 (fliA2), with 82% and 38% sequence identity, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The hptB gene encodes a histidine phosphotransfer protein involved in a complex regulatory cascade (47)(48)(49). The ⌬hptB mutant of P. aeruginosa PAK has been demonstrated to produce hyperbiofilms and to show elevated Pel polysaccharide production and elevated c-di-GMP levels (48,50).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, this protein consists of three domains: a receiver domain at its N-terminal part (CrsR D1 ), a PP2C-like serine phosphatase domain (CrsR D2 ), and an anti-sigma-like serine kinase domain (CrsR D3 ) (Fig. 1B) (36,41,42). CrsR D2 shows sequence similarity to proteins or protein domains with phosphatase activity like RsbU from B. subtilis, SypE from V. fisheri, and HsbR from P. aeruginosa (Table 1 and Fig.…”
Section: S Oneidensis Genome Contains Amentioning
confidence: 99%
“…However, in these bacteria it has not been shown that these systems are involved in the direct regulation of sigma factors. BtrWVU may post-translationally control the type III secretion system, whereas SypEA promotes biofilm formation by an unknown mechanism, with HsbRA regulating swarming motility (32)(33)(34)(35)(36)(37).…”
mentioning
confidence: 99%